EXEGETICS OF “THE CONCILIARITY” IN TARAS SHEVCHENKO’S POETRY - Bigun, O. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the research in typology of the conciliarity in Taras Shevchenko’s works and the liturgical, ecclesiastical materials, Old Ukrainian literature. The notion of conciliarity is singled out as a doctrine about the Holy Trinity. The logos ideas of the conciliarity incarnated in the Virgin are compared with «Acaphistus to the Virgin» by Romanus the Melodist, with the poems «Maria» and «Neophytus» by Taras Shevchenko. The conciliarity is reflected as a reception of the theological conception “Oneness in Christ”.